The Common European Framework of Reference for Languages: a European framework for foreign language speech development - lvalue lvalue (Universitat Jaume I. Department of English Studies, 2019)
Author/s Bettina Beinhoff Anglia Ruskin University Cambridge, United Kingdom   ABSTRACT This paper explores the representation of speech development and particularly perceptive skills in the CEFR level descriptions. The speech-related CEFR sections and related level descriptions are vague and none of the assumptions made therein (such as the supposed linear progression between levels) have been sufficiently tested yet. This paper presents an exploratory study on speech perception in language learners at different levels of proficiency and from different first language (L1) backgrounds (Spanish and German). The study is based on transcriptions in response to short narratives, and investigates what kind of influence listeners' levels of proficiency in the second language (in this case English) and their L1 backgrounds have on how intelligibility is perceived. The results suggest that proficiency levels and L1 background do indeed influence intelligibility (though not always as anticipated) and partially confirm the idea of a linear progression as proposed in the CEFR.